Rare earth elements distribution in the Gulf of Cádiz (SW Spain): geogenic vs. anthropogenic influence - Antonio Cobelo-García; Patricia Bernárdez; Clara Mendoza-Segura; Enrique González-Ortegón; David Sánchez-Quiles; Ricardo Sánchez-Leal; Antonio Tovar-Sánchez (Frontiers in Marine Science, 2024)
There is a current interest in the study of the geochemical behavior of the rare earth elements (REE) in aquatic systems since their identification as potential microcontaminants in natural waters. In this context, here we report the concentrations and patterns of dissolved REE (dREE) in the waters of the Gulf of Cádiz (GoC) and its major estuaries (Guadiana, Tinto-Odiel and Guadalquivir). Contamination in this area by metals has been extensively reported, linked to acid-mine inputs resulting from the mineralization of the Iberian Pyrite Belt, discharged mainly to the Tinto-Odiel river. However, the impact of these inputs on the concentrations and distribution of the dREE in the coastal waters of the GoC has not been addressed yet. Accordingly, elevated concentrations of dREE were obtained in the Tinto-Odiel estuary compared to the Guadiana and Guadalquivir, reflecting the impact of acid-mine drainage on this system. Only a significant fraction of anthropogenic gadolium (Gd) was observed in the Guadalquivir estuary, as a result of the input from major urban areas, where anthropogenic Gd fractions higher than 70% over the total dissolved pool were obtained for the freshwater end-member. Regarding the surface waters of the GoC, typical NE Atlantic distribution patterns of dREEs were obtained, but modified by two different end-members within this region. Accordingly, and despite the low water discharge of the Tinto-Odiel river, its elevated concentrations lead to an increase in the concentrations of dREEs in the nearshore waters of the GoC and producing a distinctive signature as observed for the MREE anomalies and HREE/LREE ratios. At the easternmost stations, close to the Strait of Gibraltar, these signals are also impacted by the inflow of Mediterranean waters and also by the discharge of the Guadalquivir river.